ANALISIS MAKNA DALAM NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI (KAJIAN SEMANTIK) - Elia Milane Nainggolan; Ayu Aldina Afriyanti (FKIP, Universitas Palangka Raya, 2023)
This research uses a qualitative approach to analyze the meaning in Leila's storytelling novel Laut. S Chudori with a semantic study. Qualitative research is research on research that is descriptive in nature and tends to use analysis. The purpose of this study is to obtain the results of an analysis of the types of meaning through semantic studies of a word, phrase or sentence as a written object contained in Leila S. Chudori's novel Laut Bercerita. Through this research, it is hoped that new insights about the analysis of meaning in the novel Laut story can be found through semantic study.